2009
DOI: 10.1080/19439340903118504
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for synthetic review of the impact of microcredit

Abstract: This paper is the protocol for a synthetic review of microfinance. The protocol describes the objectives and scope of the review, the search strategy, inclusion criteria, coding, and synthesis options.systematic review, protocol, microcredit, impact evaluation, synthetic review,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Searches were concluded on 31 December 2011. Previous searches on microcredit impact studies by team members generated close to 300 studies (see Vaessen et al, 2009) and approximately 60 studies from this database which related to women's empowerment were assessed for inclusion in the review. Searches were STEP 1: Screening (of title and abstract or in case the latter was unavailable the full text) of studies identified through the search strategy (see section 2.2.).…”
Section: Search Strategymentioning
confidence: 99%
“…Searches were concluded on 31 December 2011. Previous searches on microcredit impact studies by team members generated close to 300 studies (see Vaessen et al, 2009) and approximately 60 studies from this database which related to women's empowerment were assessed for inclusion in the review. Searches were STEP 1: Screening (of title and abstract or in case the latter was unavailable the full text) of studies identified through the search strategy (see section 2.2.).…”
Section: Search Strategymentioning
confidence: 99%
“…Previous searches on microcredit impact studies by team members generated close to 300 studies (see Vaessen et al, 2009). Approximately 60 studies were identified that were related to women's empowerment.…”
Section: Search Methods For Identification Of Studiesmentioning
confidence: 99%
“…Intervention theories with a certain degree of external validity are becoming more and more important in the context of review and synthesis work as well. 3IE is one of the organizations which is currently investing in this type of work (for an example on microcredit see Vaessen et al, 2009). 11 We still have a long way to go.…”
Section: Some Lessons For Res and Impact Evaluation From The Perspective Of A Non-randomistamentioning
confidence: 99%